2021
DOI: 10.1111/jon.12913
|View full text |Cite
|
Sign up to set email alerts
|

Arterial spin labeling compared to dynamic susceptibility contrast MR perfusion imaging for assessment of ischemic penumbra: A systematic review

Abstract: Background and Purpose: Dynamic susceptibility contrast (DSC) MR imaging is commonly used to estimate penumbra size in acute ischemic stroke; this technique relies on the administration of gadolinium contrast, which has limited use in certain populations, such as those with impaired renal function or allergies. Arterial spin labeling (ASL) is a relatively new technique that can provide information on cerebral perfusion without need for exogenous contrast agents. This systematic review examines published studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(282 reference statements)
0
7
0
Order By: Relevance
“…It is also reasonable to utilize arterial spin labeling (ASL) MRI as a noninvasive, non-contrast technique that enables not only cerebral blood flow (CBF), but also occlusion site and collateral flow evaluation [45]. In a systematic review by Liu et al the agreement on several metrics (hypoperfusion, hyperperfusion, mismatch, and reper-fusion) for ASL and DSC was concluded to be moderate to very high, with some heterogeneity of perfusion parameters in analyzed studies [46]. ASL-MRP is a valuable imaging method in certain populations with contraindications for contrast administration, including childbearing women in cases of AIS.…”
Section: Perfusion Imaging and Late Presenting Or Unknown Onset Ais P...mentioning
confidence: 99%
“…It is also reasonable to utilize arterial spin labeling (ASL) MRI as a noninvasive, non-contrast technique that enables not only cerebral blood flow (CBF), but also occlusion site and collateral flow evaluation [45]. In a systematic review by Liu et al the agreement on several metrics (hypoperfusion, hyperperfusion, mismatch, and reper-fusion) for ASL and DSC was concluded to be moderate to very high, with some heterogeneity of perfusion parameters in analyzed studies [46]. ASL-MRP is a valuable imaging method in certain populations with contraindications for contrast administration, including childbearing women in cases of AIS.…”
Section: Perfusion Imaging and Late Presenting Or Unknown Onset Ais P...mentioning
confidence: 99%
“…Indeed, Rivard et al 55 discovered that ASL underestimated CBF in hypoperfused white matter. Moreover, Liu et al 56 reported that ASL and DSC have moderate to high consistency in estimating the penumbra in AIS. This study also demonstrated that DSC had higher relative cerebral blood flow than ASL in hypoperfused areas after recanalization, whereas a comparison revealed that the findings of ASL and DSC were comparable before reperfusion, implying that ASL may underperform in the presence of minor perfusion abnormalities.…”
Section: Mr Perfusion Techniquesmentioning
confidence: 99%
“…MRI perfusion (MRP) techniques can improve selection of acute ischemic stroke patients for treatment by estimating this salvageable area of decreased perfusion. 1,2,10,14 There are several approaches to quantifying penumbra. Dynamic susceptibility contrast (DSC) MR imaging is a first-pass technique that relies on injection of a gadolinium-based contrast agent (GBCA).…”
Section: Introductionmentioning
confidence: 99%
“…DSC is commonly used to assess penumbra size in acute ischemic stroke. 8,[14][15][16][17] DSC is a very rapid scan (∼2 min), relatively robust to motion artefact, and available in most stroke centers. The main disadvantage of DSC is requiring IV contrast meaning it requires durable intravenous access for power injection of contrast, which is often unavailable in people with chronic disease or injection drug abuse history.…”
Section: Introductionmentioning
confidence: 99%